Psychology of computer use: XXXIV. The Computer Hassles Scale: subscales, norms, and reliability. - Hudiburg, Richard A. (Psychological Reports)
Data from 1199 student users formed the normative database for the Computer Hassles Scale, a 37-item scale measuring computer users' stress. The Computer Hassles Scale was scored to yield a severity of hassles score for the total scale and two subscales, Computer Runtime Errors and Computer Information Problems. The total scale and both subscales showed high internal consistency as measured by the Cronbach coefficient alpha. Guidelines for identifying high and low severity of computer users' stress were suggested. Reprinted by permission of the publisher, 1995.